INFLUENCE OF THE INTERNAL STRUCTURE OF THE BUILDING MATERIAL ON THE DRYING PROCESS - Rasuljon Tojiyev; Rajabova Nargizakhon; Muydinov Abdusamad (American Journals Publishing, 2023)
In the article, molecular physics related to the significant progress achieved at the atomic-molecular level, as well as the wide use of new physics, a deeper penetration into the essence of microprocesses in the construction processes and the consideration of corpuscular models depending on the atomic-molecular structure, molecules, atoms, ions that form wet materials, it is recommended to take into account the interaction forces between bodies.
Keywords: Molecule, atom, ions, body, process, energy, momentum, dislocation, metal, lattice, adsorption, oxygen, thermal expansion, electron, particle, crystal, evaporation zone, drying.